Policy Brief on Refugee Entrepreneurship and Skilling in Uganda - Baluku, Martin M.; Nansubuga, Florence; Nantamu, Simon; Musanje, Khamisi; Kawooya, Kenneth (RES, 2021)
Uganda is one of the refugee hosting nations, ranking 4th in 20201 behind Turkey, Colombia, and Parkistan (UNHCR, 2021a). This situation is not new to Uganda. Emigration history indicates that Uganda has been a preferred destination for refugees since the 1940s (Mulumba, 2014). Since then, the number of refugees in Uganda has been gradually increasing. Currently, Uganda hosts over 1.48 million refugees and asylum seeks (UNHCR, 2021b) in about 11 locations including Bidibidi, Adjumani, Kyangwali, Nakivale, Kyaka II, Rhino camp, Palorinya, Kampala, Imvepi, Kiryandongo, Rwamwanja, Palabek, Oruchinga, and Lobule2 . Whereas Uganda has in the past hosted refugees from different parts of the world including Europe (Mulumba, 2014), majority of the current refugee population come from neighboring countries including South Sudan, Democratic Republic of Congo (DRC), Rwanda, and Somalia (UNHCR, 2021b; Hakiza, 2014) who flee from war, poverty, hunger, and other forms of misery. Uganda’s attractiveness to refugees could be attributed to the country’s policies and culture that is friendly to foreigners. The present influx of especially South Sudanese refugees into the country starting from 2013 has given rise to the complex challenge of how to integrate the increasing number of refugees and ignited debate on feasibility of refugee policy (Hovil, 2018). Despite the attractiveness of Uganda to refugees, they face a number of unique psychosocial challenges including crowding in settlements, trauma of forced migration, and acculturation among others.
Keywords: Refugees; Psychosocial challenges